FORMATION OF HEALTH -SAVING COMPETENCE OF ELEMENTARY SCHOOL STUDENTS IN A NEW UKRAINIAN SCHOOL - Danyliak, R.Z.; Homyn, D.O. (Sworld-Us Conference proceedings, 2025)
An important task of the modern elementary school is the formation of students’ health -saving competence both within the educational process and in the conditions of various leisure activities. The concept of the New Ukrainian School involves the formati